2019
DOI: 10.1007/s00402-019-03159-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of histological and microbiological findings in septic and aseptic knee implant failure

Abstract: Introduction The Musculoskeletal Infection Society (MSIS) has defined specific clinical and laboratory criteria for the diagnosis of periprosthetic joint infection (PJI). In this study we assessed the diagnostic utility of MSIS microbiological and histological criteria for PJI in 138 cases of septic and aseptic knee implant failure. Materials and methods Intra-operative samples from 60 cases of knee septic implant failure (SIF) and 78 cases of aseptic implant failure (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A histological diagnosis is very important in the assessment of possible PJI as it forms part of the minor MSIS diagnostic criteria at a threshold of 5 PMNs per HPF [ 16 ]. A study of prosthetic knee infection concluded that knee PJI was more often confirmed by MSIS histological than microbiological criteria; thus, histology aids in distinguishing between aseptic and septic cases [ 9 ]. The AAOS recognizes that 5 PMN per HPF confers a likelihood ratio of 13.82 (7.29, 26.19); however, 10 PMN/HPF in 5 fields confers a likelihood ratio of 56.5 (20.3, 157.2) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A histological diagnosis is very important in the assessment of possible PJI as it forms part of the minor MSIS diagnostic criteria at a threshold of 5 PMNs per HPF [ 16 ]. A study of prosthetic knee infection concluded that knee PJI was more often confirmed by MSIS histological than microbiological criteria; thus, histology aids in distinguishing between aseptic and septic cases [ 9 ]. The AAOS recognizes that 5 PMN per HPF confers a likelihood ratio of 13.82 (7.29, 26.19); however, 10 PMN/HPF in 5 fields confers a likelihood ratio of 56.5 (20.3, 157.2) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inagaki et al [30] reported similarly high statistics for conventional culturing including one positive culture, producing 88.3% sensitivity, while two positive cultures decreased the sensitivity to 80%. Decreased sensitivity with two cultures could point to the presence of contamination and the inconsistency of relying on culturing to confirm PJI.…”
Section: Culturingmentioning
confidence: 93%
“…Further, although one might assume that low grade shoulder infections with pathogens such as C. acnes would produce fewer cell counts, they are, in fact, associated with high leukocyte levels [67]. Inagaki et al [30] found that almost every case of septic knee failure had 5+ neutrophils per 400x magnification in a high power field, indicating its utility visualizing both virulent and non-virulent infections. The 5+ neutrophils under histologic analysis of TKA produced 96.7% sensitivity and 100% specificity in detection of either bacterial or fungal PJI.…”
Section: Leukocytesmentioning
confidence: 99%
“…The diagnostic standards used in this study were based on the previous literature [4,12,18,20,21], as follows: PJI was diagnosed when the patient met the 2013 Musculoskeletal Infection Society (MSIS) criteria [22], or when at least one of three features was positive (intraoperative ndings including the occurrence of pus or purulent uid around the prosthesis, histological analysis, and surgical microbiological culture); AL was only diagnosed when the patient was excluded from the MSIS criteria and the intraoperative ndings, histological analysis, and microbial culture results were negative. Those who did not meet the MSIS criteria and were not con rmed to have AL through surgery were considered to have insu cient criteria for the diagnosis of AL and were excluded from our cohort.…”
Section: Methodsmentioning
confidence: 99%